2011
DOI: 10.1055/s-0031-1293205
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Anomaly and Recurrent Pregnancy Loss

Abstract: Women with recurrent pregnancy loss have a 3.2 to 6.9% likelihood of having a major uterine anomaly and a 1.0 to 16.9% chance of having an arcuate uterus. Bicornuate and septate uterine have a negative impact on reproductive outcomes and are associated with subsequent euploid miscarriage. The impact of an arcuate uterus on pregnancy outcome remains unclear. There are no definitive criteria to distinguish among the arcuate, septate, and bicornuate uteri. The American Fertility Society classification of Mülleria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 35 publications
1
29
0
10
Order By: Relevance
“…[10][11][12][13] In general, the incidence of adverse pregnancy outcomes is higher in patients with minor fusion defects and is further increased in patients with major fusion defects. 11 Interestingly, a retrospective study found that reproductive outcomes were significantly better for a given type of uterine malformation if they were associated with renal agenesis.…”
Section: Adverse Pregnancy Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12][13] In general, the incidence of adverse pregnancy outcomes is higher in patients with minor fusion defects and is further increased in patients with major fusion defects. 11 Interestingly, a retrospective study found that reproductive outcomes were significantly better for a given type of uterine malformation if they were associated with renal agenesis.…”
Section: Adverse Pregnancy Outcomesmentioning
confidence: 99%
“…7,10 There are no cohort studies that compare live birth rates in women with a history of pregnancy loss who undergo metroplasty with those who do not. Therefore, further study is needed to confirm the benefits of metroplasty in patients with no obstetric history.…”
Section: Impact Of Hysteroscopic Metroplasty On Fertility and Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Анатомические нарушения женских репродуктивных органов вызывают 10-15% случаев невынашивания беременности [18]. Доказано, что хирургические вмеша-тельства по поводу перегородки в матке, внутриматочных синехий, полипов и миом, деформирующих полость матки, значительно улучшают прогноз последующей беременности [19].…”
Section: коррекция анатомических нарушений женских репро-дуктивных орunclassified
“…Ezzel össz-hangban áll az, hogy a fejlődési rendellenességből fakadó strukturális eltérések (Müller-cső-anomáliák) arányát 8-10%-ra becsülik [10]. Más megfi gyelések szerint a habituális vetélők között a méhűri rendellenességek aránya csupán 2,2% [11], illetve 6,9% [12].…”
unclassified